2007
DOI: 10.3201/eid1310.061586
|View full text |Cite
|
Sign up to set email alerts
|

Dengue Fever Seroprevalence and Risk Factors, Texas–Mexico Border, 2004

Abstract: High seroprevalence of dengue was found on both sides of the border.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
143
3
8

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(164 citation statements)
references
References 26 publications
10
143
3
8
Order By: Relevance
“…9 Although most cases occur in the endemic areas of the Americas, Southeast Asia, and the Pacific, dengue is a threat to the continental United States; dengue cases are diagnosed each year in travelers returning from endemic areas and autochthonous cases have been documented in Texas and recently also in Florida. [10][11][12][13] New and more effective tools and approaches for surveillance and control of dengue are sorely needed. 14 In the absence of a vaccine, dengue prevention is focused upon controlling mosquito vectors.…”
Section: Introductionmentioning
confidence: 99%
“…9 Although most cases occur in the endemic areas of the Americas, Southeast Asia, and the Pacific, dengue is a threat to the continental United States; dengue cases are diagnosed each year in travelers returning from endemic areas and autochthonous cases have been documented in Texas and recently also in Florida. [10][11][12][13] New and more effective tools and approaches for surveillance and control of dengue are sorely needed. 14 In the absence of a vaccine, dengue prevention is focused upon controlling mosquito vectors.…”
Section: Introductionmentioning
confidence: 99%
“…The impact of the physical environment on infection risk has been less well-studied in high income countries perhaps because of the perception that wealth, strong public health institutions, and strong infrastructure mitigate such risks (7). For example, Brunkard et al evaluated dengue virus seroprevalence on the Texas-Mexico border and demonstrated compellingly that wealth, and the infrastructure it buys, can have important protective effects against infectious disease, even within a given geographical area (8). However, risk mitigation is not equivalent to risk elimination, and, as climate and weather continue to shift ever more rapidly, infectious disease control practitioners in high, middle, and low income countries all need to develop improved understanding of the impact such shifts may have on infectious disease epidemiology.…”
mentioning
confidence: 99%
“…En estos inciden las actuaciones del equipo de atención de salud, y la debilidad en la calidad y oportunidad de la notificación epidemiológica (1)(2)(3)(4)(5)(6)(7)(8)(9)(10).…”
Section: Introductionunclassified
“…Además, posibilitan entender la dinámica poblacional de transmisibilidad, el patrón de difusión del dengue a nivel poblacional y el acumulado de antecedente de exposición (2,4,6,7,10,13,(18)(19)(20)(21)(22)(23)(24)(25).…”
Section: Introductionunclassified